10.9k views
5 votes
Graph the function and its inverse f(x)=x^2-4

1 Answer

5 votes

Answer:

Inverse function:
y=√(x+4)

Explanation:

  • An inverse function
    f^(-1) is a function such
    f^(-1)(f(x))=x,
    for all x.
  • In practice, to find the inverse function, we just have to swich "x" by "y" in the original function, and clear y, which would be the inverse funtion.
  • In this case,
    y=f(x)=x^2-4. Then, if we swich x by y, we have the following expression:
    x=y^2-4. Now, we just have to clear y, as a function of x, by doing the following:
  1. Add 2 both sides of the equation. This would yield
    x+4=y^2.
  2. Take square root both sides of the equation. This would yield
    y=√(x+4). Then we have the inverse function!
  3. To verify the process, we replace f(x) (our original expression) into the new equation
    f^(-1)(f(x))=x, and check that equals x:
    f^(-1) is
    f^(-1)(f(x))=√((x^2-4)+4) =√(x^2) =x

Graph the function and its inverse f(x)=x^2-4-example-1
User Andrey Nikolov
by
6.4k points